Use of new approach methodologies (NAMs) to meet regulatory requirements for the assessment of tobacco and other nicotine-containing products - Miller-Holt, Jacqueline; Behrsing, Holger P.; Clippinger, Amy J.; Hirn, Carole; Stedeford, Todd J.; Stucki, Andreas O. (Frontiers in Toxicology, 2022)
Regulatory frameworks on tobacco and other nicotine-containing products (TNCP) continue to evolve as novel products emerge, including electronic nicotine delivery systems (ENDS) (e.g., electronic cigarettes or vaping products), heated tobacco products, or certain smokeless products (e.g., nicotine pouches). This article focuses on selected regulations for TNCPs that do not make health claims, and on the opportunities to use New Approach Methodologies (NAM) to meet regulatory requirements for toxicological information. The manuscript presents a brief overview of regulations and examples of feedback from regulatory agencies whilst highlighting NAMs that have been successfully applied, or could be used, in a regulatory setting, either as stand-alone methods or in a weight-of-evidence approach to address certain organ endpoints. The authors highlight the need for agencies and stakeholders to collaborate and communicate with an aim to make NAM recommendations to address specific regulatory toxicological endpoints in the future. Collaboration across sectors and geographies will facilitate harmonized use of robust testing approaches to evaluate TNCPs without animal testing.